Changes in residents' seating needs and perception of stakeholders since implementation of a provincial wheelchair program. (18th August 2021) - McEachern, D. Ross; Mortenson, W. Ben
Abstract: Background: People living in long-term care frequently have inadequate access to properly fitted wheelchairs. This can lead to potential problems with mobility, positioning, comfort, and skin integrity. A provincial programme to provide individually fitted lightweight wheelchairs to residents started in January 2016; however, no research has evaluated programme outcomes. Objectives: To identify seating needs of residents before and after implementation of a provincial wheelchair programme at two long term care facilities in Vancouver and to explore stakeholders experiences with this programme. Methods: A pre/post study design was used which involved chart reviews to collect Seating Identification Tool (SIT), and interviews with stakeholders having experience with the provincial programme to gather information on their experiences. SIT data were analysed using a Wilcoxon Signed-Rank test and interviews were analysed thematically. Findings: SIT scores improved by 2 (median) which was statistically significant for the 22 residents with pre/post data available. Prevalence of seating needs decreased on average by 18%. Among the six stakeholders interviewed, themes identified included: wheelchairs/cushions provided addressed many residents' needs; and saved residents and their families money and stress; and there is still ongoing need for more specialised equipment for frail residents (not covered by this programme). Conclusion: This study provides some evidence regarding the benefits of the introduction of this programme in two care homes and identifies potential changes that might improve wheelchair seating among residents with more severe seating needs. Further research is required on how these equipment changes might affect their mobility or participation in activities. Implications for rehabilitation: These findings appear to support the provision of lightweight individually fitted wheelchairs and moderate pressure redistribution cushions by occupational therapists in long-term care through this programme. Regular use of the SIT (i.e., on admission, condition change, annual care conference, and as needed) may be beneficial to ensure residents are properly screened for seating needs. Collaboration with the resident appears to be important to ensure equipment on provision and follow-up are meeting residents' needs. Recommend future research on the use of tilt in space wheelchairs for residents' in long-term care.